DEVELOPMENT STUDY OF A DYNAMIC PENETRASHEAROMETER FOR TESTING SOIL MECHANICAL PROPERTIES - Maghensky, Rayhan
Soil compaction is a crucial step in highway construction, as it not only affects short-term quality but also has a significant impact on the long-term performance of the infrastructure. However, field testing often encounters challenges related to time and work efficiency. To address this, the Dynamic Penetrashearometer (DPS) was developed, a tool capable of directly measuring shear strength parameters and elastic modulus in the field. The DPS is an innovative device that combines the working principles of the Dynamic Cone Penetrometer (DCP) and the Vane Shear Test, with a testing process similar to those tools. This study also involves testing soil index properties and considering the influence of effective stress on the soil. Experiments were conducted using a 60 cm x 60 cm test box filled with soil. The DPS, DCP, and Vane Shear tests were performed to verify the DPS tool. The test results indicate that variations in soil dry density (?dry) correlate with the number of blows from the DPS tool. The findings demonstrate that the DPS is an innovative alternative for improving time efficiency and accuracy in field soil strength testing, providing shear strength parameters, elastic modulus, and soil dry density (?dry), with a test correlation of R=0.909.